Death in the Emergency Department: A Retrospective Analysis of Mortality in a Swiss University Hospital. (2nd September 2019) - Heymann, Eric P.; Wicky, Alexandre; Carron, Pierre-Nicolas; Exadaktylos, Aristomenis K.
Abstract : Acute treatment in emergency medicine revolves around the management and stabilization of sick patients, followed by a transfer to the relevant medical specialist, be it outpatient or inpatient. However, when patients are too sick to be stabilized, i.e., when the care provided in the Emergency Department (ED) may not be sufficient to enable transfer, death may occur. This aspect of emergency medicine is often overlooked, and very few public data exist regarding who dies in the ED. The following retrospective analysis of the mortality figures of a Swiss university hospital from January 1st 2013 to December 31st 2016 attests to the fact that with an incidence of 2.6/1, 000, death does occur in the ED. With a broad range of aetiologies, clinical severity at presentation has a high correlation with mortality, a finding that reinforces the necessity of good triage system. Our analysis goes on to show that however (in)frequent death in the ED may be, there exists a lack of advanced directives in a majority of patients (present in only 14.8% of patients during the time of study), a worrying and often challenging situation for Emergency Medicine (EM) teams faced with premorbid patients. Furthermore, a lack of such directives may hinder access to palliative care, as witnessed in part by the fact that palliative measures were only started in 16.6% of patients during the study. The authors hope this study will serve as a stepping stone to promote further research and discussion into early identification methods for patients at risk of death in the ED, as well as motivate a discussion into the integration of palliative care within the ED and EM training curriculum.